Impact of Heat Stress on Transposable Element Expression and Derived Small RNAs in Drosophila subobscura - Bodelón, Alejandra; Fablet, Marie; de Oliveira, Daniel Siqueira [UNESP]; Vieira, Cristina; Guerreiro, Maria Pilar García (Oxford University Press (OUP), 2023)
Global warming is forcing insect populations to move and adapt, triggering adaptive genetic responses. Thermal stress is known to alter gene expression, repressing the transcription of active genes, and inducing others, such as those encoding heat shock proteins. It has also been related to the activation of some specific transposable element (TE) families. However, the actual magnitude of this stress on the whole genome and the factors involved in these genomic changes are still unclear. We studied mRNAs and small RNAs in gonads of two Drosophila subobscura populations, considered a good model to study adaptation to temperature changes. In control conditions, we found that a few genes and TE families were differentially expressed between populations, pointing out their putative involvement in the adaptation of populations to their different environments. Under heat stress, sex-specific changes in gene expression together with a trend toward overexpression, mainly of heat shock response-related genes, were observed. We did not observe large changes of TE expression nor small RNA production due to stress. Only population and sex-specific expression changes of some TE families (mainly retrotransposons), or the amounts of siRNAs and piRNAs, derived from specific TE families were observed, as well as the piRNA production from some piRNA clusters. Changes in small RNA amounts and TE expression could not be clearly correlated, indicating that other factors as chromatin modulation could also be involved. This work provides the first whole transcriptomic study including genes, TEs, and small RNAs after a heat stress in D. subobscura.
Keywords: Drosophila; heat shock stress; piRNAs; RNA-seq; stress; transposable elements